Brazil’s For-Profit Higher Education Dilemma - Knobel, Marcelo; Verhine, Robert (International Higher Education, 2017)
Brazil's higher education system is characterized by a relatively small public sector, focused on research-intensive universities, and a huge private sector, which has grown continually since the 1970s due to burgeoning demand. The private sector is now dominated by for-profit institutions which, by definition, seek immediate financial gain rather than the long-term public good. In this article, we discuss current trends with respect to for-profit institutions, giving special attention to the recent creation of mega-establishments through a series of mergers involving both national and international investors. We close by warning of some of the negative implications potentially associated with the country’s dependence on for-profit higher education.